Mechanical behaviour of the Rotokawa Andesites (New Zealand): Insight into permeability evolution and stress-induced behaviour in an actively utilised geothermal reservoir. (November 2016) - Siratovich, P.A.; Heap, M.J.; Villeneuve, M.C.; Cole, J.W.; Kennedy, B.M.; Davidson, J.; Reuschlé, T.
Highlights: We present triaxial experiments on a suite of reservoir rock at a range of different pressure conditions. Despite a brittle failure mode, high-porosity and/or highly altered rock can suffer a net porosity decrease after triaxial deformation. Brittle deformation may increase or decrease permeability, depending on sample porosity and alteration. We provide a Hoek-Brown failure criterion for typical Rotokawa Andesite. Finite element modelling shows that brittle failure of intact rock (and therefore off-fault seismicity) is unlikely during production and injection. Abstract: High-enthalpy geothermal systems, such as that of Rotokawa in the central Taupo Volcanic Zone (TVZ) of New Zealand, commonly host fracture systems that control reservoir permeability. The loss of porosity and permeability through compaction and mineral precipitation, and the opening of permeable fracture zones, occurred in tandem as the geothermal system evolved. In order to better understand how porosity can evolve in an active reservoir, a systematic study of triaxial deformation experiments has been undertaken to investigate the mechanical behaviour and failure mode of coherent andesite lavas and andesite breccias (the predominant reservoir lithologies) with varying porosity and alteration intensity from the Rotokawa Geothermal Field under high confining pressure and high pore fluid pressure conditions. These experiments provide insight into the formation of permeable fracture zones and low-permeability zones within the reservoir. Although we observed brittle failure mode in all our experiments (covering a range of rock attributes and relevant pressure conditions), we find that the amount of dilatancy during deformation, inferred to assist in the creation of a permeable network, is considerably reduced at high effective pressures and for high-porosity and highly altered samples. Importantly, some high-porosity and/or highly altered samples experienced a net compaction at the end of the experiments. Microstructural observations suggest that, although the failure mode remains ultimately brittle, microcracking and pore collapse can operate in concert at high effective pressure, porosity, and/or alteration, potentially explaining the reduction in dilatancy. We infer, therefore, that the deformation of the rocks within the reservoir could result in either a bulk permeability increase or a permeability decrease, depending on the physical characteristics of the rocks (e.g. porosity and alteration intensity) and the pressure conditions. Using our new experimental data we provide a Hoek-Brown failure criterion for an intact Rotokawa andesite with a representative porosity and show the distribution of stresses around a vertical and deviated borehole during drilling using a finite element model. Finite element modelling shows that brittle failure of intact rock (and therefore off-fault seismicity) during production and injection is unlikely in RKA containing the average porosity assumed for the reservoir. Production-induced compaction and injection-induced tensile failure could occur however in high-porosity and/or highly altered intact rock (which could lead to instability at the well boundary), particularly in deviated wells. The experiments and modelling presented herein provide insight into the evolution of an actively utilised geothermal reservoir.